Activating the paddle-wheel effect towards lower temperature in a new sodium-ion solid electrolyte, Na3.5Si0.5P0.5Se4. Issue 17 (13th April 2023) - Yang, Yu; Xu, Zhenming; Guan, Chaohong; Ouyang, Runxin; Jing, Huirong; Zhu, Hong
Abstract : Paddle-wheel mechanism dependent fast ion conduction in a new sodium solid electrolyte, Na3.5 Si0.5 P0.5 Se4 . Abstract : Designing solid electrolytes with high room temperature (RT) conductivity is essential for the development of the next generation of solid-state batteries. Beyond the static structural framework, interaction between cation mobility and anion dynamics, i.e., the paddle-wheel mechanism, may be the principle for enhanced cation mobility in solid electrolytes. Herein, we use first-principles calculations to study a promising polyanion-based solid electrolyte, Na4 SiSe4, which meets the requirements of high ionic conductivity, and thermodynamic and dynamic stability simultaneously. Ab initio molecular dynamics reveal the fast Na diffusion dominated by the paddle-wheel mechanism, which is rationalized by the coupling of the translational motion of Na with the rotational motion of SiSe4 in terms of time-space, vibrational properties, and energetics. Furthermore, by substituting Si with P, we theoretically predict Na3.5 Si0.5 P0.5 Se4 with the paddle-wheel effect activated at 600 K, while Na4 SiSe4 is activated at 1000 K. The calculated RT ionic conductivities of Na3.5 Si0.5 P0.5 Se4 is up to 16.94 mS cm −1 . Our findings highlight that high cation mobility can be achieved by exploiting the anion rotation to invoke the paddle-wheel effect, especially in the low temperature range.